Trends in Sustainable Buildings and Infrastructure - Yepes, Víctor; Navarro Martínez, Ignacio J. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The recently established Sustainable Development Goals call for a paradigm shift in the way that buildings and infrastructures are conceived. The construction industry is a major source of environmental impacts, given its great material consumption and energy demands. It is also a major contributor to the economic growth of regions, through the provision of useful infrastructure and generation of employment, among other factors. Conventional approaches underlying current building design practices fall short of covering the relevant environmental and social implications derived from inappropriate design, construction, and planning. The development of adequate sustainable design strategies is therefore becoming extremely relevant regarding the achievement of the United Nations 2030 Agenda Goals for Sustainable Development. This book comprises 11 chapters that highlight the actual research trends in the construction sector, aiming to increase the knowledge on sustainable design practices by highlighting the actual practices that explore efficient ways to reduce the environmental consequences related to the construction industry, while promoting social wellbeing and economic development. The chapters collect papers included in the Special Issue "Trends in Sustainable Buildings and Infrastructure" of the International Journal of Environmental Research and Public Health.